2007
DOI: 10.1186/1741-7015-5-32
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of N-acetylcysteine in contrast-induced nephrotoxicity: unsupervised clustering to resolve heterogeneity

Abstract: Background: Meta-analyses of N-acetylcysteine (NAC) for preventing contrast-induced nephrotoxicity (CIN) have led to disparate conclusions. Here we examine and attempt to resolve the heterogeneity evident among these trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 103 publications
1
71
0
5
Order By: Relevance
“…NAC has mainly been studied in the setting of contrast nephropathy following the initial publication by Tepel et al [213] which provided the catalyst for the subsequent proliferation of similar studies [127, [213][214][215][216][217][218][219][220][221][222]. This subject continues to generate much research and has led to several meta-analysis [152, [223][224][225][226][227][228] (ESM Table S9). Most report a risk reduction, although study heterogeneity and positive reporting bias somewhat hinders definitive recommendations [229].…”
Section: Rationalementioning
confidence: 99%
“…NAC has mainly been studied in the setting of contrast nephropathy following the initial publication by Tepel et al [213] which provided the catalyst for the subsequent proliferation of similar studies [127, [213][214][215][216][217][218][219][220][221][222]. This subject continues to generate much research and has led to several meta-analysis [152, [223][224][225][226][227][228] (ESM Table S9). Most report a risk reduction, although study heterogeneity and positive reporting bias somewhat hinders definitive recommendations [229].…”
Section: Rationalementioning
confidence: 99%
“…Daha sonraki çalışmalarda NAC oral düşük doz, oral yüksek doz ve intravenöz yollarla kullanılarak karşılaştırılmıştır. Ancak çalışmalarda ve metaanalizlerde çelişkili sonuçlar elde edilmiştir (6) .…”
Section: Yazışma Adresiunclassified
“…Because animal studies have indicated that NAC may protect the myocardium and preserve kidney function [128], it was expected to prevent CIN in humans. After the report by Tepel et al [65] on the effect of NAC (600 mg twice daily, orally) in preventing CIN, many RCTs and meta-analyses were conducted [129][130][131][132][133][134][135][136][137][138][139].…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%
“…Although this meta-analysis concluded that NAC was more renoprotective than was saline hydration alone, the sample sizes of the studies analyzed and the quality of sample calculation methods used in the meta-analysis were questioned. In another meta-analysis of 22 RCTs, Gonzales et al [138] used a modified L'Abbé plot to divide the data into cluster 1 (18 studies, 2,445 patients) and cluster 2 (4 studies, 301 patients), and reported that cluster 1 studies showed no benefit, while cluster 2 studies indicated that NAC was highly beneficial. However, cluster 2 studies were published earlier, and were of lower quality as measured by Jadad scores (\3, three study characteristics combined) [138,139].…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%
See 1 more Smart Citation